ANÁLISE DAS PROPRIEDADES RADIATIVAS DE TRÊS TINTAS ACRÍLICAS E UMA TINTA NATURAL APLICADAS A TRÊS SUBSTRATOS - Dal Soglio, Carolina Rodrigues; Meller, Bruna Just; Olinger, Marcelo Salles; Güths, Saulo; Marinoski, Deivis Luis; Mizgier, Martin Ordenes (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The radiative properties of the envelope surfaces have a significant impact in the building's thermal performance. In the present study, thermal properties (emittance and reflectance of solar radiation) of one natural paint and four conventional paints were measured. The paints were applied on three substrates: metal, ceramic and wood. The properties were verified through laboratory tests. The solar reflectance measures were performed using a reflectometer and a spectrophotometer UV-Vis-NIR, according to the ASTM standards C1549-09 and E903-12, respectively. The portable emissometer was used for thermal emittance measurements, according to the ASTM standard C1371-15. The results show that the difference between the reflectance values measured by the equipments is up to 6%. The influence of the substrates was higher for the natural paint samples, presenting a relative variation of 6%. It was concluded that the reflectance of the natural paint throughout the different wavelengths behaves differently from the conventional paints. The natural paint showed higher reflectance for UV and IR, despite the relatively lower values of reflectance for waves in the visible spectrum.